DESAIN DAN IMPLEMENTASI PEMBELAJARAN FULL DAY SCHOOL DALAM PENGEMBANGAN KEMANDIRIAN SISWA - Anis Fauzi; Lilis Solihah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2019)
The independence of learning is very important to apply in the environment and educational institutions through the design and implementation of a full day school learning system. Children of school age who is experiencing a period of growth and development of language and social relationships require wider to develop social concepts. This research is a Mixed Research study using Sequential Merge forms. The researcher used both studies in sequence. Primary data from this study were obtained from the results of observations and interviews with research subjects consisting of principal, vice principal of Curriculum Field, Educators, and Staff, Students, School Committees and Parents. Secondary data in this study are books, research journals, or articles related to this research, as well as supporting documents in this study. In this study the authors took a sample of 10% of the population, thus getting 50 students. Data obtained from the results of the questionnaire discussion are processed using a Likert scale. Data analysis in qualitative research is carried out when data collection takes place, and after data collection, and after completion of data collection in a certain period. The results of this study are: First, Islamic Senior High School 2 of Serang City combines the National Curriculum (2013 Curriculum) and Islamic School Curriculum; Secondly, Islamic Senior High School 2 has not been full day if they see the characteristics of a full day five working days, but at the level of practice the learning burden has exceeded full days, not to mention there is a teaching and learning program held at the Boarding School; Third, learning the independence of students is carried out inside and outside the classroom for competitive advantage, whereas for more cooperative excellence it is obtained in the boarding school.